2017
DOI: 10.1016/j.preghy.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Various levels of circulating exosomal total-miRNA and miR-210 hypoxamiR in different forms of pregnancy hypertension

Abstract: The level of circulating exosomal total-miRNA and hsa-miR-210 was elevated in women with PE, and it was higher in the severe form. We showed that hsa-miR-210 is secreted via exosomes, which may have a role in the pathomechanism of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…The total miRNA concentration in exosome samples was six times higher in sever PE and three times higher in moderate PE groups compared with normotensive group. Moreover, exosomal has‐miR‐210‐3p expression was higher in both sever PE and moderate PE groups and in sever PE higher than moderate PE group …”
Section: Epigenetic Changes In Pementioning
confidence: 90%
See 1 more Smart Citation
“…The total miRNA concentration in exosome samples was six times higher in sever PE and three times higher in moderate PE groups compared with normotensive group. Moreover, exosomal has‐miR‐210‐3p expression was higher in both sever PE and moderate PE groups and in sever PE higher than moderate PE group …”
Section: Epigenetic Changes In Pementioning
confidence: 90%
“…Moreover, exosomal has-miR-210-3p expression was higher in both sever PE and moderate PE groups and in sever PE higher than moderate PE group. 106…”
Section: Has-mir-210 Has-mir-517c Changes In Exosome Ago-bound Plamentioning
confidence: 99%
“…A number of publications have addressed placental EVs and their potential role in pregnancy and its complications . Several ex vivo (eg, placental perfusion) and in vivo systems have been used as a source of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that miR‐210 is upregulated and regulated by HIF in a variety of tumors and cardiovascular diseases and is associated with oxidative stress, mitochondrial metabolism, angiogenesis, DNA repair, and cell survival (Devlin, Greco, Martelli, & Ivan, ). MiR‐210 was found to be consistently upregulated in the placenta and plasma of PE in most studies (Biro et al, ; Enquobahrie et al, ; Munaut et al, ; Noack et al, ; Xu et al, ). Laser microdissection analysis revealed that miRNA‐210 is predominantly present in syncytiotrophoblasts (Ishibashi et al, ).…”
Section: Mirna Involved In Pementioning
confidence: 95%